2021
DOI: 10.1016/j.scitotenv.2020.143068
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 water sector responses in Europe: A scoping review of preliminary governmental interventions

Abstract: The unprecedented scale and impact of COVID-19 pandemic, and the accompanying lockdown implemented across many countries, has exacerbated water scarcity and security globally. Many European governments have introduced policy interventions to mitigate and protect their economies. Yet, water resources, which are a potential enabler in revitalising Europe’s economy, have received few of such policy interventions since the World Health Organization declared the COVID-19 outbreak as a public health emergency only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 18 publications
0
47
0
1
Order By: Relevance
“…According to our study, security and access to water were affected during the contingency, which strengthens the evidence on the importance of this item for food security. Despite the challenges that the contingency has presented worldwide, it is necessary to prioritize strategies focused on security and access to water where institutions, governments and civil society participate to protect this human right [27].…”
Section: Discussionmentioning
confidence: 99%
“…According to our study, security and access to water were affected during the contingency, which strengthens the evidence on the importance of this item for food security. Despite the challenges that the contingency has presented worldwide, it is necessary to prioritize strategies focused on security and access to water where institutions, governments and civil society participate to protect this human right [27].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of water and virus control is generally accepted and practiced, not only in drink water, but in daily water hygiene as well. The challenges of water availability, accessibility, and quality still remain a matter both in developing and developed countries because of impact of COVID-19 pandemic [36] , [37] , [38] . Meanwhile, water can play an important role in revitalizing the economy after COVID-19 [37] .…”
Section: Bibliometric Tracking Of the Investigation Trends Since Outbmentioning
confidence: 99%
“…Despite the level of concern about the impact of Covid-19 on water systems a review of governmental responses in 27 European countries (Antwi et al, 2021) revealed that COVID-19 pandemic policy measures were focused around economic measures, but water, which plays a significant role in both socio-economic and well-being, enjoyed limited interventions. Some countries had water-related interventions predominately consisting of short-term measures to ensure uninterrupted water supply and to cushion the impact of loss of income during the pandemic.…”
Section: International Context To Observations From the Case Study In Istanbul Water Usementioning
confidence: 99%